Evaluation of video-assisted HPV education in government-supported clinics in Western Kenya. - Haley Dion; Hanul Choi; Michelle Huang; Laya Sathyan; Emily Herfel; Breandan Makhulo; Jeniffer Ambaka; Saduma Ibrahim; Megan Huchko (PLOS Global Public Health)
Despite prevalent preventative methods of human papillomavirus (HPV), cervical cancer remains the foremost cause of cancer-related death among women of reproductive age in Western Kenya. HPV self-sampling is a preventative measure that can improve accessibility and availability to cervical cancer screening. Correct education about HPV is crucial to combating stigma and increasing HPV screening uptake. In this study, we evaluated the workflow impact of a video-assisted HPV education to promote self-sampling in clinical settings in Kisumu, Kenya. We conducted a descriptive workflow study nested in a two-part cluster-randomized control trial in six government-supported health clinics in Kisumu County. We observed the workflow of HPV screening video-assisted and standard health educations. and evaluated community and clinic health assistant facilitation (CCHA), duration, and feasibility of the intervention. Thirty HPV screening-eligible women who participated in the video intervention were recruited for three focus group discussions (FGDs). The FGDs aimed to better understand women's experience with the video screening, their impressions on the content, and feedback about intervention logistics. Across 33 observations, 16.5 women per day watched the educational video at intervention clinics, and 14 women per day heard standard Ministry of Health cervical cancer prevention education talks at control clinics. Sixty-three percent of women participated in HPV self-sampling in the intervention sites, compared to forty-six percent who screened after standard health talks at control sites. The workflow observations identified variable video projection and viewing space, access to power supply, and CCHA availability and ability to utilize the projector as major factors impacting education workflow. Women in FGDs appreciated the video modality, length of video, and education location. HPV video education is a suitable intervention, with further research recommended to determine the viability of sustainably implementing the intervention in a clinic environment. This research is fully funded by the Duke University Global Health Institute.